Constructing an Eco-Conscious Identity through Metaphors: Muhammadiyah’s Environmental Discourse on Its Official Website - Suswandi, Irwan; Zulferdi, Lazuar Azmi; Lailiyani, Putri Nirma (Jurnal Bahasa dan Sastra, 2026)
The discourse on environmental preservation (hifz al-bi’ah) emerged in response to worsening environmental conditions. There is a view that hifz al-bi’ah is one dimension of the maqasid al-shari’ah (the objectives of sharia in Islam). As one of the largest mass organizations, Muhammadiyah is a highly effective platform for promoting understanding and awareness of environmental preservation. This will also affect the image of Muhammadiyah as an environmentally conscious organization. This study aims to analyze the forms of images related to environmental preservation (hifz al-bi’ah) within the Muhammadiyah. This research is categorized as an analytical-descriptive research, with the selected data collection method being the observational method using the tapping technique. The collected data were analyzed using distributional method with immediate constituent analysis (ICA) technique, and referential method with determinant element sorting (DES) technique. The data source used in this study is the Muhammadiyah.or.id website, with the data narrowed to articles written directly by the Muhammadiyah.or.id Editorial Team. The theory used is ecolinguistics as outlined by Stibbe (2015). The result is that 22 data in the form of phrases and clauses discussing environmental issues, of which 14 present the image of Muhammadiyah as an organization in beneficial metaphor and 8 in ambivalent metaphor. From these data, it is concluded that Muhammadiyah news is dominated by the organization’s environmental consciousness (beneficial), with an image of an organization that is educative, innovative, collaborative, driving, responsible, and implementative in environmental matters. In addition, Muhammadiyah also positions the environment as a places, organisms and networks.